BEYOND THERAPEUTIC BENEFITS: KAJIAN FARMAKOVIGILANS EFEK SAMPING KORTIKOSTEROID DI INDONESIA - Senya Puteri Amalia; Farida Istiqamah; Nur Ainah; Desy Ayu Lestari (Jurnal Insan Farmasi Indonesia, 2026)
Corticosteroids are widely used in clinical practice in Indonesia for the treatment of various diseases. However, prolonged and/or high-dose corticosteroid therapy may lead to serious adverse effects that negatively affect patients’ quality of life. Monitoring of corticosteroid-related adverse drug reactions in Indonesia remains limited, highlighting the need for a pharmacovigilance approach to identify, assess, monitor, and prevent undesirable drug-related events. This review aimed to provide a comprehensive overview of adverse effects associated with corticosteroid use in Indonesia as a basis for safe, effective, and rational therapeutic decision-making. Literature searches were conducted through ScienceDirect, PubMed, Google Scholar, and manual searches using the keywords “pharmacovigilance,” “corticosteroid,” “side effect,” “adverse effect,” and “Indonesia” based on predefined inclusion and exclusion criteria. A total of eight eligible articles were critically analyzed, covering various corticosteroid dosage forms, patient characteristics, and the types and severity of adverse effects. The findings showed that adverse reactions ranged from mild to severe, with increased risk associated with long-term and high-dose corticosteroid use. This review emphasizes the importance of pharmacovigilance in improving healthcare professionals’ awareness and promoting rational corticosteroid use in Indonesia